Dynamic Model for Flow and Droplet Deposition in Direct Ceramic Ink-jet Printing - Mythili, Vijay Soundararajan; Prakasan, K. (Defence Science Journal, 2004)
A rapid fabrication technique, for building microceramic parts, using a dropon-demand ceramic ink-jet printer is currently under development. This finds application in producing ceramic cores for gas turbines, space applications, and ceramic hybrid electromechanical systems. Another application is in the use of intelligent inks, in which particles assemble themselves so as to interrupt the signals in a particular direction and to produce a suitable output for tactical applications. An attempt has been made to develo a mathematical model for dro leflo rmation from orifice and itsdewsition on subsmate. The distributidn of energy supplied to the pi zoelectrica ctuator in the ink-jet p&t head is modelled and ejected droplet parameters (diameter and velocity) were related to the force imparted by the piezodisc. This model was extended to develop a relation for maxlmum droplet spread that occurs during impact. h p l e t spread determines the lateral resolution of the system and the thickness of each deposited layer.